Motivations for Using Religious Digital Media: A Hierarchical Regression Analysis Among Jordanian University Students - Thalgi , Mohammad Jaber (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2024)
This study investigated the factors influencing motivations for using religious digital media (RDMUM) among 330 Jordanian university students through hierarchical regression analysis. The analysis revealed that demographic factors, particularly age and gender, significantly predicted motivation, with younger individuals and males showing higher engagement. Educational level, explicitly having a BA degree, also influences motivation, whereas university location and specialization do not have significant effects. The type of digital media used (websites, social media, podcasts) does not significantly impact motivation, although a negative association with Twitter suggests that platform-specific characteristics may affect engagement. Prior knowledge and specific interests in Islamic thought, faith, and jurisprudential topics are strong motivators that highlight the importance of content relevance and depth. The final model, which explains 49% of the variance in the RDMUM, underscores the robust explanatory power of the included variables. These findings emphasize the need for tailored content to address user interests and knowledge levels. Content creators and practitioners can leverage these insights to develop more engaging and effective religious digital media, ultimately enhancing users’ engagement and satisfaction. Moreover, this study's potential to inspire and guide future research in this field is significant and contributes to the academic community's understanding of religious digital media.